Brecht e o cinema: uma análise metodológica em contexto fílmico - Barreto, Luciana Moura (2017)
The main purpose of this study is to analyse the different method executions from Brecht in the cinema. This concerns more particularly on finding the strangeness effect, as proposed in Brechtian epic theatre, in the context of the following group of cinematographic achievements scripted by the playwright himself: Zeitprobleme:wie der Arbeiter wohnt (1930; How the berliner worker lives), by Slatan Dudow, Kuhle Wampe oder: Wem gehort die Welt? (1932; Kuhle Wampe or Who owns the worls?) by Slatan Dudow and Hagmen also die! (1943) by Fritz Lang. The theoretical references are from Brechtian doctrinaire along his main enshrined studies, for instance, those studies proposed by playwrights like Fredreric Ewen, Walter Benjamin, Frederic Jameson and, in Brazil, Gerd Bornheim and Fernando Peixoto. In addition to this first theoretical position about theory of cinema and works of filmic analysis, such as Eisenstein, Robert Stam, Jacques Aumont, Laurente Jullier, Michel Marie, Michèle Lagny and, in Brazil, Ismail Xavier. It will be considered theatrical elements which are part of the studied filmography as well as text, music, players acting, scenario, clothing, camera angle and installation, trying to highlight the existence of Brechtian methodology in these film productions